Endoscopic endonasal management of esthesioneuroblastoma: A retrospective multicenter study. Issue 2 (April 2018) - Nakagawa, Takayuki; Kodama, Satoru; Kobayashi, Masayoshi; Sanuki, Tetsuji; Tanaka, Shuho; Hanai, Nobuhiro; Hanazawa, Toyoyuki; Monobe, Hiroko; Yokoi, Hidenori; Suzuki, Motohiko; Yamashita, Masaru; Omori, Koichi
Abstract: Objective: The aim of the present study was to illustrate the safety and utility of the endoscopic endonasal approach (EEA) for the treatment of esthesioneuroblastomas (ENB). Methods: We retrospectively reviewed patients with a diagnosis of ENB between March 2008 and February 2016 at 10 tertiary referral hospitals in Japan, and assessed demographic data, stage of disease, surgical approach, outcomes and postoperative complications. Results: A total of 22 patients (10 males and 12 females; mean age at presentation, 49.0 years) underwent endoscopic endonasal resection of newly diagnosed ENBs. Dulguerov staging at presentation was T1, 6 patients; T2, 9 patients; T3, 5 patients; and T4, 2 patients. As surgical procedures, unilateral resection via EEA was performed in 12 patients aiming preservation of the contralateral olfactory system, and bilateral resection via EEA was done in 10 patients. Post-operative radiotherapy was done in 20 patients. Pathological margin studies revealed margin-free resections in 21 patients (95.5%). The mean period of follow-up was 44 months. Local recurrence was observed in one T2 patient 12 months after bilateral resection. All patients were alive at the last follow-up, and 21 patients showed no evidence of disease. No post-operative complications including bleeding, CSF leak and meningitis were identified. Preservation of olfactory function was achieved in 11 patients (91.7%). Conclusion: The results of the present study indicate the safety and utility of multilayer resection using EEA for treatment of ENBs.